A new multiple flights routing and scheduling algorithm in terminal manoeuvring area - Bae, Sangjun; Shin, Hyo-Sang; Lee, Chang-Hun; Tsourdos, Antonios (IEEE, 2018)
We address multiple flights planning problems from its initial waypoint to its destination while satisfying the minimum separation requirement between each aircraft at all times in a Terminal Manoeuvring Area (TMA) to maintain or increase runway throughput. Due to operational constraints for safety, most of the current aircraft fly over or by waypoints, and along nominal routes in the airspace. Where the waypoints and routes in the airspace can be modelled as a weighted digraph, called airspace graph. We propose a problem that consists of determining a flight path (routing problem) and its speed profile (scheduling problem) in a given airspace graph in which a time-based weighting scheme of the airspace graph is proposed to reflect a speed-limitation-compliant schedule that satisfy the minimum separation requirement. For multiple flights cases, the flight paths and schedules are obtained by iteratively solving the problem for each flight by applying the First Come First Served (FCFS) algorithm to determine an arrival sequence. The main contributions of this paper are increasing a solution search space by solving two problems simultaneously, efficient computational time, and providing the separation-compliant flight path and speed profile within the speed limitation for each flight. We demonstrate the advantages of the proposed approach through a case study in which multiple flights arrive at a single airport, and we compare the results with Regulated Tactical Flight Model (RTFM) obtained from EUROCONTROL Demand Data Repository 2 (DDR2). Although, we consider only a single airport and make an assumption to simplify flight routes from holding stacks to a Final Approach Fix (FAF), the results show the potential usage of the proposed algorithm as a Decision Support Tool (DST) for Air Traffic Controllers (ATCOs) if the following considerations are taken into account: detailed routes-based flights after the holding stacks, multiple airports, departing aircraft, all possibe aircraft types, and uncertainties produced by external sources.